Factors associated with the intention of pregnant women to give birth with epidural analgesia: a cross-sectional study - Luka Van Leugenhaege; Julie Degraeve; Yves Jacquemyn; Eveline Mestdagh; Yvonne J. Kuipers (BMC, 2023)
Abstract Background In Belgium most women receive epidural analgesia during labour. Although, it offers satisfactory pain relief during labour, the risk on a series of adverse advents has been reported. The objective of this study was to determine factors associated with the intention of pregnant women, anticipating a vaginal birth, of requesting epidural analgesia during labour. Methods A cross-sectional study, using an online self-report questionnaire was performed, including socio-demographic and personal details. Associated factors were examined with the HEXACO-60 questionnaire, the Mental Health Inventory-5, the Tilburg Pregnancy Distress Scale and the Labour Pain Relief Attitude Questionnaire for pregnant women. The level of intention to request epidural analgesia was based on two questions: Do you intend to ask for epidural analgesia (1) at the start of your labour; (2) at some point during labour? Data were collected predominantly during the second and third trimester of pregnancy. Descriptive analysis and a multiple linear regression analysis were performed. Results 949 nulliparous (45.9%) and multiparous (54.1%) pregnant women, living in Flanders (Dutch-speaking part of Belgium) anticipating a vaginal birth completed the questionnaires. Birth-related anxiety (ß 0.096, p < 0.001), the attitude that because of the impact of pregnancy on the body, asking for pain relief is normal (ß 0.397, p < 0.001) and feeling more self-confident during labour when having pain relief (ß 0.034, p < 0.001) show a significant positive relationship with the intention for intrapartum epidural analgesia. The length of the gestational period (ß − 0.056, p 0.015), having a midwife as the primary care giver during pregnancy (ß − 0.048, p 0.044), and considering the partner in decision-making about pain relief (ß − 0.112, p < 0.001) show a significant negative relationship with the intention level of epidural analgesia. The explained variability by the multiple regression model is 54%. Conclusions A discussion during pregnancy about the underlying reason for epidural analgesia allows maternity care providers and partners to support women with pain management that is in line with women's preferences. Because women's intentions vary during the gestational period, pain relief should be an issue of conversation throughout pregnancy.